Effects of hypoxia/hyperoxia exposure on immune function – results from a spacecraft-relevant hypobaric chamber study - Crucian, Brian; Diak, Douglass M.; Garbino, Alejandro; Gutierrez, Cody; Bustos-Lopez, Sara; Colorado, Audrie; Young, Millennia; Smith, Scott M.; Zwart, Sara R.; Oswald, Thomas M.; Hew-Yang, Monica Y.; Estep, Patrick; et al. (Frontiers in Physiology, 2025)
IntroductionAlthough the International Space Station provides a normoxic environment, deep space missions are expected to leverage a hypobaric, mildly hypoxic living environment to facilitate frequent extravehicular activities EVAs, aka spacewalks. Although hypoxia may be experienced terrestrially, it will be atypical for human physiology to live in hypobaric/hypoxic conditions yet frequently experience hyperoxic stress due to EVAs. It is well established that hypoxia induces dysregulation of the human immune system, in generally a sensitized/proinflammatory fashion. This is primarily evidenced from studies of individuals living at altitude.MethodsTo ascertain the effect of hypoxic/hyperoxic shifts on immunity, a series of 11 days hypobaric chamber studies were conducted at the Johnson Space Center. The living environment consisted of 8.2–9.6psi/28.5%–34% oxygen, and there were several simulated EVAs which were performed under hypobaric/hyperoxic conditions consisting of 4.3psi/85%–95% oxygen. For the current sub-study, biosamples were collected before and after simulated EVAs to ascertain the effects of hypoxia, decompression and hyperoxic stress on immunity. The sub-study consisted of 3 chamber tests, 23 total subjects.ResultsShifts in leukocyte distribution, function, and plasma cytokine concentrations were associated with atmospheric shifts, primarily after the hypobaric/hyperoxic EVA activities. Astronauts already experience immune system dysregulation due to microgravity, stress, and other mission influences.DiscussionThese data indicate that, similar to living at high altitude, altered atmosphere exposure in a pressurized vehicle environment may dysregulate human immunity which may be exacerbated by EVAs. The additive effects of hypoxia, in concert with other spaceflight mission variables, on clinical risks for astronauts must be better characterized to enable future exploration class space missions.